2016
DOI: 10.1144/jgs2015-121
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphic and geological constraints on the active normal faulting of the Gediz (Alaşehir) Graben, Western Turkey

Abstract: Abstract:The Gediz (Alaşehir) Graben is located in the highly tectonically active 14 and seismogenic region of Western Turkey. Extension due to regional geodynamic 15 controls has resulted in broadly two-phase evolution of the graben; firstly, low-angle The Gediz (Alaşehir) Graben is the northernmost graben of a series of East-West trending 30 neotectonic grabens in western Turkey that dissect the Menderes Massif (Fig. 1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 69 publications
1
38
0
Order By: Relevance
“…Detrital apatite fission track data show that the southern margin of the Gediz Graben experienced two major exhumation events, one involving the whole margin during late Miocene and one involving only its western part (Salihli area) during Plio‐Quaternary times, thus generating a differential uplift of this sector (Asti et al, ). This differential exhumation is consistent with the differential evolution of slip rates on faults bounding the southern margin of the modern graben in response to fault segments interaction and linkage (Kent et al, , ).…”
Section: Geological Settingsupporting
confidence: 80%
See 1 more Smart Citation
“…Detrital apatite fission track data show that the southern margin of the Gediz Graben experienced two major exhumation events, one involving the whole margin during late Miocene and one involving only its western part (Salihli area) during Plio‐Quaternary times, thus generating a differential uplift of this sector (Asti et al, ). This differential exhumation is consistent with the differential evolution of slip rates on faults bounding the southern margin of the modern graben in response to fault segments interaction and linkage (Kent et al, , ).…”
Section: Geological Settingsupporting
confidence: 80%
“…Another possibility to explain the localization of the Plio‐Quaternary exhumation event deals with the evolution of faulting at the southern margin of the basin. Kent et al (, ) showed that active fault segments bounding the southern margin of the modern Gediz Graben became connected during the last 2.6–2 Myr, thus resulting in an increase in throw rates along the Salihli segment of this fault system. This increase in throw rate might have also played a role in the differential exhumation of the Gediz detachment in the Salihli area.…”
Section: Discussionmentioning
confidence: 99%
“…The height of the knickpoints above the fault correlates well with the relative values of footwall relief and total throw on the active high‐angle normal faults bounding the graben, which were first presented in Kent et al (). In that study, Kent et al ., compared fault throw measurements, derived from structural and seismic analysis, with the topographic relief in the Gediz Graben between the valley floor and the top of the exhumed basin sediments along the southern margin.…”
Section: Resultsmentioning
confidence: 99%
“…(A) Simplified geological map of the Western Anatolian Extensional Province (adapted from Bozkurt, , ; Seyitoğlu et al ., ; Çemen et al, ; Kent et al, ); the box shows the location of Figures and . GG, Gediz Graben; KMG, Küçük Menderes Graben; BMG, Büyük Menderes Graben; DKBF, Datça–Kale Breakaway Fault (Seyitoğlu et al ., ), also known as the South West Anatolian Shear Zone (Çemen et al, ).…”
Section: Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation